2022
DOI: 10.1021/acs.jchemed.2c00637
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Electrometallurgical Recycling of Metals from Waste Printed Circuit Boards via Slurry Electrolysis Using Benign Chemicals

Abstract: The rapid growth of personal electronics has promoted a surge of e-waste worldwide. Among the e-waste stream, waste printed circuit boards (WPCBs) contain a lot of recyclable valuable metals that can incentivize the recycling operation when recovered. This pedagogical exercise demonstrates a simple electrocatalytic metal recovery strategy that works at room temperature and atmospheric pressure. Students can complete the exercise within 1.5–2 h and get to learn about electrocatalytic reactions and their paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…32,33 However, conventional SE practice requires a highly acidic, alkaline, or oxidative environment, such as 4 mol L −1 HCl, 34 190 36 1 mol L −1 (NH 4 ) 2 S 2 O 8 , 37 glycine, 38 and some of the mixed ionic liquid solution being used as the electrolyte (H 2 SO 4 and [MIm]HSO 4 ), 39 to facilitate the metal leaching from WPCB composite and prevent the metal ions from precipitating as electrochemically inert metal (hydro)oxide. Besides strong acids, organic solvent systems were 41 Our group recently reported the use of ethylene glycol (EG) as the main solvent for electrochemical leaching and recovery of metals from powdered WPCBs, 42,43 and He et al also has reported that EG could strengthen the stability of H 2 O 2 , which is better for Cu leaching. 44 Although effective and pH-neutral, EG displays relatively high toxicity with a lethal dose (LD) of 1.4−1.6 mL kg −1 ; accidental ingestion of EG could be fatal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…32,33 However, conventional SE practice requires a highly acidic, alkaline, or oxidative environment, such as 4 mol L −1 HCl, 34 190 36 1 mol L −1 (NH 4 ) 2 S 2 O 8 , 37 glycine, 38 and some of the mixed ionic liquid solution being used as the electrolyte (H 2 SO 4 and [MIm]HSO 4 ), 39 to facilitate the metal leaching from WPCB composite and prevent the metal ions from precipitating as electrochemically inert metal (hydro)oxide. Besides strong acids, organic solvent systems were 41 Our group recently reported the use of ethylene glycol (EG) as the main solvent for electrochemical leaching and recovery of metals from powdered WPCBs, 42,43 and He et al also has reported that EG could strengthen the stability of H 2 O 2 , which is better for Cu leaching. 44 Although effective and pH-neutral, EG displays relatively high toxicity with a lethal dose (LD) of 1.4−1.6 mL kg −1 ; accidental ingestion of EG could be fatal.…”
Section: Introductionmentioning
confidence: 99%
“…Sebastián et al described the Cu electro-crystallization in a DES (eutectic mixture of choline chloride and urea 1:2) . Our group recently reported the use of ethylene glycol (EG) as the main solvent for electrochemical leaching and recovery of metals from powdered WPCBs, , and He et al also has reported that EG could strengthen the stability of H 2 O 2 , which is better for Cu leaching . Although effective and pH-neutral, EG displays relatively high toxicity with a lethal dose (LD) of 1.4–1.6 mL kg –1 ; accidental ingestion of EG could be fatal .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in recent years, a large number of papers have been published describing laboratory activities to acquire skills and knowledge in this field. For example, laboratory activities have been developed for the valorization of electronic waste. , Also, laboratory activities have been proposed for the recycling of waste from the food industry and waste from biomass and plastic recycling . In all of these works, the importance of the scientific and technical knowledge that students acquire in their academic training for the implementation of processes based on the concepts of circular economy in accordance with the principles of sustainable development is evident.…”
Section: Introductionmentioning
confidence: 99%
“…A change of paradigm is necessary to reduce the ecological impact of the electronics sector. The change requires that all actors become involved: producers, sellers/vendors, consumers, governments, academia, nongovernmental organizations, etc. These participants need to take an agentive stance. , Education is a vector of paradigm change. As for other global challenges, the change of paradigm in the electronics sector requires educational approaches where basic sciences, engineering, design, economics, social sciences, medical sciences, and policy making share knowledge, needs, challenges, perspectives, and possible solutions.…”
Section: Introductionmentioning
confidence: 99%